Cheerfulness and life satisfaction mediated by self-esteem and behavioral activation: A serial mediation model. (1st November 2020) - Lau, Chloe; Chiesi, Francesca; Hofmann, Jennifer; Ruch, Willibald; Saklofske, Donald H.
Abstract: The benefits of cheerfulness, as a mood state and personality trait, are widespread in the literature concerning subjective well-being and physical health. While robust findings in the literature have shown positive affect and more positive, lighthearted uses of humor are associated with self-esteem, no study has investigated the role of self-esteem and behavioral activation in the trait cheerfulness and well-being association. The present study bridges this gap through testing a double mediation path model in a sample of undergraduate students ( N = 391) on the effects of self-esteem and behavioral activation on the trait cheerfulness and life satisfaction association. As predicted, self-esteem and behavioral activation, both independent and serially, mediated the positive association between cheerfulness and life satisfaction (SWL). These results suggest that trait cheerfulness predicts higher self-esteem and behavioral activation, which subsequently predicts SWL. Pairwise comparisons amongst the three indirect effects suggest that trait cheerfulness predicting self-esteem and subsequently SWL was significantly larger than the other two effects. Overall, these results provide new insight that may advance a coherent and multifaceted theoretical framework on the pathways in which cheerfulness may enhance psychological well-being.